The Influence Of Job Rotation And Work Teams On Employee Performance - Rusli, Sastri Mandayani; Jasman, Jumawan; Riyanti, Riyanti (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study involved all employees of PT Indomarco Prismatama, and the purpose of this study was to determine how job rotation and work teams affect employee performance. Design/methodology/approach: The study used a saturated sample and collected 44 respondents who had all the necessary data to test. This research data comes from a survey conducted to employees and processed using the SPSS version 25 program. Findings: The results showed that job rotation has no effect and is not significant on employee performance, while work teams have an effect and are significant on employee performance. Research limitations/implications: This study also has several limitations such as difficulty in obtaining respondents who are willing to fully participate in the study. Practical implications: Companies can improve employee performance by implementing effective job rotation and forming cohesive work teams. Job rotation can prevent burnout and improve employee skills, while cohesive work teams can strengthen collaboration and productivity. Thus, management needs to consider optimal rotation and team building strategies to achieve better employee performance. Originality/value: This title has significant originality as it combines two important variables in human resource management, namely job rotation and work teams, and analyzes their impact specifically on employee performance. The value of this title lies in the potential of the research to provide new insights into how job rotation strategies and work team dynamics can influence employee productivity and effectiveness in an ever-evolving work environment. Paper type: Research paper